Current Approaches in Treatment of Diabetic Retinopathy and Future Perspectives - Kutluturk Karagoz, Isil; Allahverdiyev, Adil; Bagirova, Melehat; Abamor, Emrah Sefik; Dinparvar, Sahar (MARY ANN LIEBERT, INC, 2020)
Diabetes mellitus (DM) is a metabolic disease, which is the most common cause of low vision in developing countries and affects almost all systems of the body. In view of the increase in DM prevalence in the world, it would not be a surprise that diabetic retinopathy (DR) and other vascular complications related to diabetes become a serious public health problem. Currently, vascular endothelial growth factor, laser photocoagulation, and intravitreal steroids are the mainstays for DR treatment, but the efficacy of these treatment strategies remains insufficient. Therefore, new treatment modalities for DR have been developed, such as stem cell therapies, extracellular vesicular system, and nanodrug delivery systems. Although there have been several reviews in the literature on the treatment of DR, we have not confronted any review that has the titles of all these topics. With this review, we aim to present the pathophysiology of DR and to review the current and promising new treatment methods based on stem cells, extracellular vesicular system, and nanodrug delivery systems for the future of DR management.
Keywords: diabetic retinopathy; nanotechnology; VEGF; MESENCHYMAL STEM-CELLS; NANOSTRUCTURED LIPID CARRIERS; ENDOTHELIAL PROGENITOR CELLS; VEGF TRAP-EYE; TRIAMCINOLONE ACETONIDE; INTRAVITREAL INJECTION; OCULAR DELIVERY; DRUG-DELIVERY; MACULAR EDEMA; PHYSICOCHEMICAL CHARACTERIZATION; Ophthalmology; Pharmacology & Pharmacy